2015
DOI: 10.1016/j.scitotenv.2014.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Continued implication of the banned pesticides carbofuran and aldicarb in the poisoning of domestic and wild animals of the Canary Islands (Spain)

Abstract: Although nowadays the intentional poisoning of domestic and wild animals is a crime in EU, in the past the poison was used in rural areas of a number of European countries to kill animals that were considered harmful for human activities. In Spain evidences indicate that intentional poisonings continue to occur throughout the entire country nowadays. This situation seems to be of particular concern in the Canary Islands (Spain), where this study was performed. Our results confirmed that 225 animals were poison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 19 publications
6
70
0
3
Order By: Relevance
“…Furadan 3G (2, 3-dihydro-2, 2-dimethyl-7-benzofuranyl methylcarbamate) is used as a broad spectrum systemic carbamate pesticide for agriculture.Although, it is already banned in the United States and some European countries (Ruiz-Suárez ., 2015), it is still used as a potent crop protection chemical in most of the Indian states (Mishra and Sharma, 2011). Furadan 3G is one of the preferred pesticides used to protect crops by killing insects, nematodes and parasites (Wandan ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furadan 3G (2, 3-dihydro-2, 2-dimethyl-7-benzofuranyl methylcarbamate) is used as a broad spectrum systemic carbamate pesticide for agriculture.Although, it is already banned in the United States and some European countries (Ruiz-Suárez ., 2015), it is still used as a potent crop protection chemical in most of the Indian states (Mishra and Sharma, 2011). Furadan 3G is one of the preferred pesticides used to protect crops by killing insects, nematodes and parasites (Wandan ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aldicarb, an N-methyl carbamate pesticide, has many hazardous effects on humans and animals [2] [3]. In the past decades, control actions to ban or severely restrict aldicarb use have been achieved by Europe and other countries due to its toxic effects [4]. However, aldicarb is still used in agriculture in some developing countries including China [5] [6].…”
mentioning
confidence: 99%
“…Nevertheless, it has been shown that legal and commercial restrictions have not influenced the intentional illegal use of some pesticides as poisons [16,17]. For this reason for the selection of the 109 pesticides included in this multiresidue method we have mainly taken into account their known toxicities for either humans and other mammals (Table 1), and also according to the available data, the frequency with which these compounds have been implicated in human poisonings [14,15], regardless of whether their use is currently allowed or not.…”
Section: Pesticide Selectionmentioning
confidence: 99%
“…This methodology is based on a liquid-liquid extraction, clean-up, chromatographic separation, and detection by QqQ operated in the MRM mode, and has been successfully applied to the detection of the toxicant involved in 2 recent cases of poisoning by an unknown pesticide that were submitted to our laboratory. Besides, this methodology has been also applied in our laboratory to the identification of the pesticides in matrices other than blood [16].…”
Section: Introductionmentioning
confidence: 99%